2018
DOI: 10.1002/adfm.201802003
|View full text |Cite
|
Sign up to set email alerts
|

Gate‐Induced Massive and Reversible Phase Transition of VO2 Channels Using Solid‐State Proton Electrolytes

Abstract: The use of gate bias to control electronic phases in VO 2 , an archetypical correlated oxide, offers a powerful method to probe their underlying physics, as well as for the potential to develop novel electronic devices. Up to date, purely electrostatic gating in 3-terminal devices with correlated channel shows the limited electrostatic gating efficiency due to insufficiently induced carrier density and short electrostatic screening length. Here massive and reversible conductance modulation is shown in a VO 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 33 publications
3
41
0
1
Order By: Relevance
“…Since the ionic liquid contains an amount of trace water, the hydrolysis reaction will occur under high gate voltages. The required oxygen ions can come from this hydrolysis . When a stimulus spike is applied on the presynaptic neuron, it triggers an excitatory postsynaptic current (EPSC) in the SCO channel.…”
Section: Resultsmentioning
confidence: 99%
“…Since the ionic liquid contains an amount of trace water, the hydrolysis reaction will occur under high gate voltages. The required oxygen ions can come from this hydrolysis . When a stimulus spike is applied on the presynaptic neuron, it triggers an excitatory postsynaptic current (EPSC) in the SCO channel.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 19 h, a reversible MIT of VO 2 is demonstrated from the temperature-dependent plate resistance ( R s ) in VO 2 -based ILs FET at different gate voltages. What is more, Jo et al [ 143 ] used solid-state proton electrolyte to achieve a reversible MIT of VO 2 at room temperature. A large number of H + ions were effectively injected into VO 2 channel under gate bias voltage without oxygen defects.…”
Section: Properties and Related Applications Of Vomentioning
confidence: 99%
“…As we know, hydrogen is the smallest and lightest atomic element, which can effectively insert or remove the gap position of VO 2 , thereby modulating the MIT behavior [ 143 , 160 ]. The research results of Yoon et al [ 160 ] demonstrated that VO 2 stabilizes in the metal phase at a low hydrogen concentration, and the hydrogenated insulating phase (note as HVO 2 phase) occurs again at a high hydrogen concentration.…”
Section: Properties and Related Applications Of Vomentioning
confidence: 99%
“…Recently, in situ control of electronic carrier through ion transport in nanoscale has been attracting attention for nanoelectronics devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Physical properties such as electronic conductivity, magnetoresistance and superconducting critical temperature were tuned by the similar method [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The redox transistor employs electrochemical carrier doping by electrochemical reduction and oxidation (redox) due to the ion transport.…”
Section: Introductionmentioning
confidence: 99%